Pengaruh Pajak Hotel, Pajak Restoran, Pajak Hiburan, Pajak Parkir Terhadap Pendapatan Asli Daerah Dimoderasi Oleh Kepatuhan Wajib Pajak Pada Badan Pendapatan Daerah Kabupaten Malang - Supriyatna, Hardiyati; Sari, Ati Retna; Made, Anwar (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to examine the relationship between hotel tax, restaurant tax, entertainment tax, and parking tax in relation to the increase in local revenue (PAD) driven by the growth of the tourism and culinary sectors in Malang Regency. The study also explores how taxpayer compliance can regulate the relationship between regional taxes and local revenue. The primary objective of this research is to determine the impact of the four types of regional taxes on local revenue and to assess the extent to which taxpayer compliance influences the efficiency of tax collection. The relationship between variables, based on the research hypothesis, is explained using an explanatory/confirmatory quantitative approach. The subjects of this research are the seven technical implementation units for the collection of hotel tax, restaurant tax, entertainment tax, and parking tax in Malang Regency from 2017 to 2021. Data quantification and analysis of the variables were conducted using a quantitative method. The results show that hotel tax, restaurant tax, parking tax, and entertainment tax have a positive impact on PAD, although this increase is dependent on the level of taxpayer compliance as a moderating variable.